2012
DOI: 10.1186/1471-2458-12-1096
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the MacArthur scale of subjective social status - Brazilian Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: BackgroundThe MacArthur Scale of Subjective Social Status intend to measure the subjective social status using a numbered stepladder image. This study investigated the reliability of the MacArthur scale in a subsample of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil).MethodThree scales were employed using different references: 1) the overall socioeconomic position; 2) the socioeconomic situation of the participant’s closer community; 3) the workplace as a whole. A total of 245 of the ELSA parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 27 publications
2
118
0
4
Order By: Relevance
“…Information regarding each participant's education level (high school or lower vs college or above) was collected during the ARIC visit 1 interview. Subjective economic status was measured based on the MacArthur scale,34 a self‐estimated rank of the family financial status compared to the whole US population and ranked into 10 categories (rank score 1 [lowest] to 10 [highest]), and lower economic status was defined as having a rank score <6 (median score among study participants). The subjective economic status has demonstrated a good predictability for health status 35.…”
Section: Methodsmentioning
confidence: 99%
“…Information regarding each participant's education level (high school or lower vs college or above) was collected during the ARIC visit 1 interview. Subjective economic status was measured based on the MacArthur scale,34 a self‐estimated rank of the family financial status compared to the whole US population and ranked into 10 categories (rank score 1 [lowest] to 10 [highest]), and lower economic status was defined as having a rank score <6 (median score among study participants). The subjective economic status has demonstrated a good predictability for health status 35.…”
Section: Methodsmentioning
confidence: 99%
“…Das bietet gegenüber der subjektiven Schichteinstufung den Vorteil, dass die Befragten nicht unbedingt eine Vorstellung vom Modell sozialer Schichtung haben müssen, um die Frage zu beantworten [28]. Besonders für internationale Vergleiche bzw.…”
Section: Hintergrundunclassified
“…Besonders für internationale Vergleiche bzw. den Einsatz des Instruments in unterschiedlichen Bevölke-rungsgruppen kann dies von Vorteil sein [28,29]. Inzwischen wurde die MacArthur Scale in verschiedene Sprachen über-setzt und hinsichtlich klassischer Testgü-tekriterien überprüft.…”
Section: Hintergrundunclassified
See 1 more Smart Citation
“…An instrument in the shape of a social ladder, (27), was used to assess perceived social status. There are two versions of the ladder and the one used in this study was the society ladder which has shown good test-retest stability (28). The participants were asked to imagine that a ladder with ten steps represented the social status and hierarchy of people in society.…”
Section: The Macarthur Scale Of Subjective Socialmentioning
confidence: 99%